Evaluation of the degradation potential of different advanced oxidation processes for a textile dye mixture: a kinetic study with mathematical modeling and toxicological tests - Silva, Joanna Cysneiros; Santana, Rayany Magali da Rocha; Nascimento, Graziele Elisandra do; Lucena, Alex Leandro Andrade de; Silva, Ana Maria Ribeiro Bastos da; Sá, José Luís Ferreira; Melo, Ana Maria Mendonça de Albuquerque; Napoleão, Daniella Carla; Duarte, Marta Maria Menezes Bezerra (Ciência e Natura, 2020)
Studies and research have been developed around the world on environmental pollution. Among the most diverse types of pollutants, textile dyes have attracted attention in the Brazilian Northeast. These compounds, besides being persistent, resist to the conventional treatments applied in the wastewater treatment plants. Thus, the present study evaluated the degradation of the mixture of direct red 23, direct red 227 and direct orange 26 dyes by advanced oxidation processes (AOPs). It was observed that the homogeneous AOPs were more efficient, being able to degrade 100% of the chromophoric groups after the optimization of the variables [H2O2], [Fe] and pH. The reaction kinetics for the photo-Fenton process followed a pseudo-first order non-linear model, with rapid decay of the concentrations in the first 60 min. Aiming to have a methodology capable of predicting the degradation efficiency for the studied processes, it was verified that the artificial neural networks MLP 4-9-3 and MLP 5-6-3 well represent the data from the homogeneous and heterogeneous processes, respectively. A toxicity study was carried out using seeds, bacteria and microcrustaceans and it was found that the intermediate compounds formed during the treatment process act differently for each of them.